1996
DOI: 10.1002/(sici)1096-8628(19960202)61:4<396::aid-ajmg17>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Human growth hormone treatment in prepubertal children with achondroplasia

Abstract: We studied the effects of recombinant human growth hormone (GH) treatment in 6 prepubertal children with achondroplasia. The patients' age ranged from 2 11/12 to 8 5/12 years and the GH dose was of 0.1 IU/kg/day subcutaneously. Auxological assessments and bone age determinations were performed 6 months before, at the beginning, and after 6 and 12 months of therapy. The growth velocity increase during the whole year of treatment ranged from 1.1 to 2.6 cm/year in 3 patients while in the others no variation was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The same finding was reported by Stamoyannou et α/. 11 , no signs of acromegaly were found after GH treatment. In the study of Weber et α/.…”
Section: Effect Of Gh On Glucose Tolerancesupporting
confidence: 89%
See 1 more Smart Citation
“…The same finding was reported by Stamoyannou et α/. 11 , no signs of acromegaly were found after GH treatment. In the study of Weber et α/.…”
Section: Effect Of Gh On Glucose Tolerancesupporting
confidence: 89%
“…According to Weber et al 11 , oral glucose tolerance tests were normal both before and after 12 months of GH treatment in patients with achondroplasia. The same finding was reported by Stamoyannou et α/.…”
Section: Effect Of Gh On Glucose Tolerancementioning
confidence: 96%
“…Growth velocity was increased by a factor of 2.3, being greatest in children with the lowest pretreatment growth velocities, in agreement with our data. Finally, Weber et al [1996] treated six prepubertal children with achon- Fig. These investigators observed an increase in HV, from a mean (± SD) of 4.1 (0.8) to 7.2 (1.4) cm/year.…”
Section: Discussionmentioning
confidence: 93%
“…GH administration was thought to be ineffective for the treatment of children with achondroplasia; how-ever, since development of biosynthetic GH, a number of studies have demonstrated that when GH is given in dosages of 0.5-1.0 IU/kg/week, an increase in height velocity (HV) can be achieved [Horton et al, 1992;Nishi et al 1993;Yamate et al, 1993;Hä genä s 1994;Weber et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…Growth hormone plays an important role in regulating linear skeletal growth by promoting chondrocyte proliferation directly or indirectly through insulin-like growth factor-1. The majority of growth hormone trials in children with achondroplasia have been short-term [46][47][48][49][50][51][52]. These studies report an increase in growth velocity (65-75%) during the first year or a gain of 0.2-0.5 SD of height during the first year of treatment.…”
Section: Treatmentmentioning
confidence: 96%